High-flow nasal cannula oxygenation reduces desaturation during percutaneous radiofrequency ablation under moderate sedation - Wang, Jiangling; Wu, Qicheng; Ding, Zewu; Zhang, Wen; Xie, Kangjie; Mao, Xiaochun; Fang, Xiangming (Frontiers in Medicine, 2025)
BackgroundThe majority of percutaneous radiofrequency ablation (PRFA) procedures for liver cancer are performed under ultrasound guidance and with moderate sedation. Oxygen desaturation is one of the most common and concerning adverse events that can be challenging to prevent during this procedure. High-flow nasal cannula (HFNC) oxygen therapy is effective in delivering high oxygen flow rates. This study aimed to evaluate the safety of HFNC oxygen therapy in preventing oxygen desaturation in patients undergoing ultrasound-guided PRFA with moderate sedation.MethodsIn this prospective, randomized controlled study, 100 patients who underwent ultrasound-guided PRFA with moderate sedation were randomly divided into two groups: a low-flow oxygen group (6 L/min via an HFNC) and a high-flow oxygen group (40 L/min via an HFNC). The primary outcome was oxygen desaturation. Other adverse events were also recorded.ResultsPatients who received high-flow oxygen (40 L/min) had a lower incidence of mild desaturation (0% vs. 6%, p = 0.24), moderate desaturation (4% vs. 30%; RR 7.5, 95% CI 2.07, 28.58, p = 0.0009), and severe desaturation (0% vs. 4%, p = 0.5) compared to those who received low-flow oxygen (6 L/min). Average oxygen saturation (SpO2) was significantly higher in the high-flow group (p < 0.0001). No significant differences were observed in other adverse events or perioperative variables.ConclusionIn patients undergoing ultrasound-guided PRFA with moderate sedation, high-flow oxygen therapy at 40 L/min through HFNC therapy resulted in higher average oxygen saturation levels and a reduced incidence of oxygen desaturation—particularly moderate and severe desaturation—compared to low-flow oxygen therapy at 6 L/min.Clinical trial registrationIdentifier NCT05212064.